2016
DOI: 10.1007/s13197-016-2399-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of gelatinized flour fraction on thermal and rheological properties of wheat-based dough and bread

Abstract: This work considered gelatinized wheat flour fraction with properties similar to hydrocolloid to enhance the strength of dough network by improving water retention and rheological characteristics. The gelatinized (90°C ) fraction of the wheat flour was incorporated in the dough formulation at different levels (5, 10, and 20% w/w). The effects of the gelatinized flour (GF) fraction on the dough rheology and thermal properties were studied. The incorporation of GF induced a moderate increase of dough viscoelasti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 35 publications
0
10
0
1
Order By: Relevance
“…The lack of utilization of lactose by S. cerevisiae reduces the production of CO 2 during fermentation in lactose enriched dough. In addition to that, the relatively higher amount of sugar remained in dough may delay the gelatinization of starch (Beleia, Miller, & Hoseney, 1996) and subsequently cause a reduction of CO 2 gas retention in bread (Carrillo‐Navas et al., 2016; Sumnu, Ndife, & Bayındırlı, 2000). These may result in a harder texture with lower volume for lactose enriched bread leavened by S. cerevisiae .…”
Section: Resultsmentioning
confidence: 99%
“…The lack of utilization of lactose by S. cerevisiae reduces the production of CO 2 during fermentation in lactose enriched dough. In addition to that, the relatively higher amount of sugar remained in dough may delay the gelatinization of starch (Beleia, Miller, & Hoseney, 1996) and subsequently cause a reduction of CO 2 gas retention in bread (Carrillo‐Navas et al., 2016; Sumnu, Ndife, & Bayındırlı, 2000). These may result in a harder texture with lower volume for lactose enriched bread leavened by S. cerevisiae .…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the Δ H values required for melting the gluten depend on the extent of network structure aggregation and the internal available water. 37 Therefore, KGM II molecules could interact easily with the other components of the dough. Finally, addition of KGM II provided a more coherent microstructure of the dough or a better water distribution in dough network capable of undergoing thermal resistance.…”
Section: Resultsmentioning
confidence: 99%
“…Control, NB and MB breads possessed a fine and closely-packed pore distribution, whereas EB bread crumb presented larger and heterogeneous cells. Carrillo-Navas, et al (2016) found a more heterogeneous crumb microstructure of (larger and heterogeneous gas cells) of bread containing gelatinized flour. This occurrence could be explained based on the thicker cell walls observed through SEM in MB and EB crumbs (supplementary material 4), which has been previously reported to result in coarser cell structures (Gorton, 2009).…”
Section: Physical Properties Of Breadsmentioning
confidence: 89%
“…On the other hand, the drop in the specific volume with the addition of extruded banana starch could be due to the slightly higher cold viscosity property of gelatinized starch compared to native counterparts, as observed in the pasting profile (supplementary material 2). This event would increase dough consistency and limit the mobility of gases and other dough components and ultimately limit dough expansion (Carrillo-Navas et al, 2016).…”
Section: Physical Properties Of Breadsmentioning
confidence: 99%
See 1 more Smart Citation